2018
DOI: 10.19045/bspab.2018.700195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hot water treatments and storage period on the quality attributes of banana (Musa sp.) fruit

Abstract: The current study was carried out to evaluate the effect of hot water treatments and storage period on quality attributes of banana in the laboratory of Farm Structures, Sindh Agriculture University, Tandojam, Pakistan during 2017. Green matured Basari banana fruit free from defects was collected from local fruit market. The samples of banana fruit were dipped for 10 minutes in four different water treatments i.e. control (T1), 40°C (T2), 50°C (T3) and 60°C (T4). The quality attributes of stored banana fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
5
4
0
Order By: Relevance
“…The results from the present study showed that hot water-treated dates exhibited lower moisture content that might be attributed to the accelerated respiration and transpiration rates. Our results are in agreement with those of a previous study that reported that banana fruit dipped in hot water at 60 °C exhibited lower moisture content due to this regulating the respiration and transpiration rates [ 30 ]. Moreover, it was observed that hot water at 70 °C significantly increased the loss of moisture contents in date fruit [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results from the present study showed that hot water-treated dates exhibited lower moisture content that might be attributed to the accelerated respiration and transpiration rates. Our results are in agreement with those of a previous study that reported that banana fruit dipped in hot water at 60 °C exhibited lower moisture content due to this regulating the respiration and transpiration rates [ 30 ]. Moreover, it was observed that hot water at 70 °C significantly increased the loss of moisture contents in date fruit [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The higher SSC and lower acidity in hot water-treated date cultivars might be due to modification of sugar and acid metabolism. Our results are also in accordance with previous findings suggesting that higher SSC and lower TA contents were found in hot water-treated banana [ 30 ], strawberry [ 35 ], tomato, and apple [ 36 ]. Ascorbic acid has comparatively lower stability and is more likely to decrease in fruits and vegetables subjected to heat treatment [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The highest fruit weight loss was from control Hachiya fruits, while the least fruit weight loss was from Fuyu fruits that were dipped in 40°C hot water and packaged in vacuum packaging (table 1). The higher weight loss in control fruits were due to the upsurge in the respiration rates by fruits during the storage, accelerated evaporation rate from surface of fruits and burning of tissues of fruit surfaces [16].…”
Section: Fruit Weight Loss (%)mentioning
confidence: 96%
“…Similarly, the weight loss percentage PLOS ONE was 13.9% in control banana after 21 days, 21.5% at 28 days and 33% at 32 days of storage and they became non-edible. This could be linked to the reduced moisture retaining ability of un treated banana due to accelerated rate of transpiration and respiration from banana surface as well as deterioration in tissues of banana peel [62], while the weight loss percentage showed less increase as 10.8%, 12.8%, 12.8%, 11.6% and 16.8% with 0.01%, 0.02%, 0.03%, 0.04% and 0.05% AgNPs respectively at 32 days of storage (Fig 13). The results are similar to the previous work where AgNPs synthesized from tea extract increased the weight loss percentage with increase in storage period in cherry tomatoes for 15 days [63].…”
Section: Plos Onementioning
confidence: 99%